Assessment of the Effect of Oral Health on Quality of Life and Oral-Health Indicators among ESRD Patients in Southwest Florida: A Pilot Study - Payal Kahar; Carol Chapman; Jayanta Gupta (International Journal of Dentistry)
Purpose. To determine and compare OHRQoL (oral-health-related quality of life) using the Geriatric Oral Health Assessment Index (GOHAI-12) and Oral Health Impact Profile (OHIP-14) among patients receiving hemodialysis (HD). Methods. Face-to-face interviews and intraoral examinations were conducted among 70 patients. Mann–Whitney U test and Kruskal–Wallis test were used to compare each item score with demographics and dental and overall health status. Results. The mean number of years on dialysis was 4.7 ± 7.5 yrs; the mean number of teeth present was 19.7 ± 11.04; median values of OHRQoL using GOHAI-12 and OHIP-14 were 52 and 64. Within GOHAI-12, limiting food (p 0.043), uncomfortable eating in front of people (p 0.045), limiting contact with people (p 0.046), and eating without discomfort (p 0.011) were significantly associated with females. Being worried (p 0.040) and self-conscious (p 0.048) were significant for age groups ≤65 years. Prevented from speaking was associated with >20 teeth (p 0.016). Being worried about oral health was associated with number of years on dialysis (p 0.042). Within OHIP-14, speech was associated with number of teeth present (p 0.024). Total inability to function was significantly associated with race (p 0.018), number of teeth (p 0.028), and edentulousness (p 0.031). Conclusions. GOHAI-12 was more effective than OHIP-14 in assessing OHRQoL. However, most subjective experiences did not correlate with clinical findings. Systemic health issue like end-stage renal disease affecting QoL might have taken precedence over dental problems. Clinical assessments should be inherent in oral-health evaluation and there should be cooperation between nephrologists and dentists in promoting oral health and treating systemic conditions among HD patients.